Ensino de conceitos geométricos e astronômicos contextualizado na obra “Planolândia: um romance de muitas dimensões” - Santos, Alailton Damião Oliveira (2019)
The teaching of many concepts of Geometry is being neglected or has received superficial treatment in basic schooling in Brazil. The causes may be related to curricular reforms, such as the one that occurred with the Modern Mathematics movement, with the lack of preparation of teachers, time or even with the ignorance of the importance of the development of the spatial notion and geometric thinking of students. Deficiencies in the understanding of concepts of geometry causes difficulty in geometric abstraction and decreases the ability to interpret and represent space. Therefore, our research problem was to think about what activities can be developed with a view to developing in students a better understanding of Spatial Geometry. Aiming to accomplish interventions in order to contribute to an improvement in the understanding of geometric concepts, methodological strategies were developed in order to assist in the development of the notion of spatiality of students, with the use of sensory experiments and theoretical elements of Astronomy from the book “Planolândia” by Edwin Abbott. Within an interventionist methodological perspective, the research was aimed at high school students from the Colégio Estadual de Barrocas - Ba. In this sense, the proposal consisted of carrying out a set of actions that led to the realization of five activities involving themes related to the concept of spatiality guided by clippings from the book Planolândia, contextualized with Astronomy topics. With the applications it was possible to discuss elements of bi and three-dimensional space, promoting greater familiarity with geometric terms for a better understanding of the concepts of coordinated axes, Cartesian plane, flat and spatial geometric figures and of space according to the Theory of General Relativity. Throughout the methodological strategy planning process, specific experimental materials related to each activity were created. In this way, the educational products generated in this work are the didactic kits, consisting of the experimental materials developed to be used in the activities and an activity notebook, composed of methodological strategies capable of promoting the study of geometric concepts, contributing to the expansion of the spatial notion of students.